HMGA2 interacts with KAT6A to regulate MMPs chromatin architecture and promote triple-negative breast cancer metastasis - Qiao, Lu; Liang, Zenghua; Ma, Pengyi; Zhang, Shanshan; Sun, Cuiyun; Luo, Wenjun; Yu, Lin (Frontiers in Immunology, 2025)
BackgroundTriple-negative breast cancer (TNBC), the most lethal breast cancer subtype, demonstrates poor prognosis due to its high rates of metastasis, recurrence, and mortality. The metastatic potential in TNBC patients serves as a critical determinant of clinical outcomes. The high mobility group AT-hook 2 (HMGA2) has emerged as a novel chromatin architectural regulator, its specific role in TNBC metastasis requires further investigation.MethodsWe analyzed the expression of HMGA2 in TNBC and non-TNBC patients using Genomic Data Commons (GDC) The Cancer Genome Atlas (TCGA) and immunohistochemistry. The correlation between HMGA2 expression and patient prognosis was assessed using the Kaplan-Meier estimator. The roles of HMGA2 in TNBC metastasis were validated through cell wound healing assay, transwell assay and lung metastatic model. RNA sequencing, chromatin immunoprecipitation, DNA electrophoretic mobility shift, co-immunoprecipitation and chromosome conformation capture assays were applied to identify the mechanisms by how HMGA2 functions as a novel chromatin architectural regulator.ResultsOur study revealed significantly upregulated HMGA2 expression in TNBC patients compared to non-TNBC patients. Kaplan-Meier survival analysis demonstrated a strong association between elevated HMGA2 expression and poor prognosis in TNBC cases. Functional studies showed that HMGA2 downregulation markedly inhibited TNBC metastatic progression. Mechanistic investigations revealed that HMGA2 facilitates TNBC metastasis through transcriptional activation of matrix metalloproteinases (MMPs). Specifically, HMGA2 interacted with lysine acetyltransferase 6A (KAT6A) to mediate histone acetylation at MMPs promoter regions. Concurrently, HMGA2 induced chromatin conformation changes to enhance MMPs transcriptional activity.ConclusionThese findings establish that the HMGA2/KAT6A complex promote MMPs expression to drive TNBC metastasis, identifying novel therapeutic targets for this aggressive malignancy.